High frequency of WNT-activated medulloblastomas with CTNNB1 wild type suggests a higher proportion of hereditary cases in a Latin-Iberian population - Moreno, Daniel Antunes; Bonatelli, Murilo; Antoniazzi, Augusto Perazzolo; de Paula, Flávia Escremim; Leal, Leticia Ferro; Garcia, Felipe Antônio de Oliveira; de Paula, André Escremim; Teixeira, Gustavo Ramos; Santana, Iara Viana Vidigal; Saggioro, Fabiano; Neder, Luciano; Valera, Elvis Terci; et al. (Frontiers in Oncology, 2023)
Purpose: Medulloblastomas are the most common primary malignant brain tumors in children. They are divided into molecular subgroups: WNT-activated, SHH-Activated, TP53 mutant or wild type, and non-WNT/non-SHH (Groups 3 and 4). WNT-activated medulloblastomas are usually caused by mutations in the CTNNB1 gene (85-90%), and most remaining cases of CTNNB1 wild type are thought to be caused by germline mutations in APC. So far, the frequencies of CTNNB1 have been reported mainly in North-American and European populations. The aim of this study was to report the frequency of CTNNB1 mutations in WNT-activated medulloblastomas in a Latin-Iberian population and correlate with their clinicopathological characteristics. Methods: Two-hundred and sixty-six medulloblastomas from seven different institutions from Brazil (n=211), Portugal (n=38), and Argentina (n=17) were evaluated. Following RNA and DNA isolation from FFPE tumor tissues, the molecular classification and CTNNB1 mutation analysis were performed by nCounter and Sanger sequencing, respectively. Results: WNT-activated accounted for 15% (40/266) of the series. We observed that 73% of WNT-activated medulloblastomas harbored CTNNB1 mutations. CTNNB1 wild type cases (27%) were more prevalent in females and suggested be associated with a worse outcome. Among the CTNNB1 wildtype cases, the available analysis of family history revealed two cases with familiar adenomatous polyposis, harboring APC germline variants. Conclusion: We observed a lower incidence of CTNNB1 mutations in WNT-activated medulloblastomas in our Latin-Iberian cohort compared to frequencies previously described in other populations. Considering that CTNNB1 wild-type cases may exhibit APC germline mutations, our study suggests a higher incidence (~30%) of hereditary WNT-activated medulloblastomas in the Latin-Iberian population.